tutorstate (tutorstate) wrote,
tutorstate
tutorstate

integrate 1/(sinx + cosx) dx

integrate 1/(sinx + cosx) dx


maybenow.com
∫ [1 /(cosx + sinx)] dx = multiply and divide the integrand by (cosx - sinx): ∫ {(cosx - sinx) /[(cosx + sinx)(cosx - sinx)]} dx = expand the denominator: ∫ [(cosx - sinx) /(cos²x - sin²x)] dx = break it up into: ∫ [cosx /(cos²x - sin²x)] dx + ∫ [- sinx /(cos²x - sin²x)] dx = rewrite the first denominator in terms of sinx and the second one in terms of cosx: ∫ {cosx /[(1 - sin²x) - sin²x]} dx + ∫ {- sinx /[cos²x - (1 - cos²x)]} dx = ∫ [cosx /(1 - sin²x - sin²x)] dx + ∫ [- sinx /(cos²x - 1 + cos²x)] dx = ∫ [cosx /(1 - 2sin²x)] dx + ∫ [- sinx /(2cos²x - 1)] dx (#) let us solve the first integral substituting sinx = t hence (differentiating both sides) d(sinx) = dt → cosx dx = dt, yielding: ∫ cosx dx /(1 - 2sin²x) = ∫ dt /(1 - 2t²) = factor the denominator as a difference of squares: ∫ dt /{1 - [(√2)t]²} = ∫ dt /{[1 - (√2)t][1 + (√2)t]} = decompose it into partial fractions: 1 /{[1 - (√2)t][1 + (√2)t]} = A/[1 - (√2)t] + B/[1 + (√2)t] 1 /{[1 - (√2)t][1 + (√2)t]} = {A[1 + (√2)t] + B[1 - (√2)t]} /{[1 - (√2)t][1 + (√2)t]} 1 = A + (√2)At + B - (√2)Bt 1 = (√2)(A - B)t + (A + B) hence: | (√2)(A - B) = 0 | A + B = 1 | A = B | B + B = 1 | A = 1/2 | B = 1/2 yielding: 1 /{[1 - (√2)t][1 + (√2)t]} = A/[1 - (√2)t] + B/[1 + (√2)t] = (1/2)/[1 - (√2)t] + (1/2)/[1 + (√2)t] thus the integral becomes: ∫ [1 /(1 - 2t²)+ dt = ∫ {{(1/2)/[1 - (√2)t]} + {(1/2)/[1 + (√2)t]}} dt = break it up pulling constants out: (1/2) ∫ {1 /[1 - (√2)t]} dt + (1/2) ∫ {1 /[1 + (√2)t]} dt = divide and multiply the first integral by (-√2), and the second one by (√2) so as to make each numerator the derivative of the respective denominator: (1/2)(-1/√2) ∫ {(-√2) /[1 - (√2)t]} dt + (1/2)(1/√2) ∫ {(√2) /[1 + (√2)t]} dt = [- 1/(2√2)] ∫ d[1 - (√2)t] /[1 - (√2)t]} + [1/(2√2)] ∫ d[1 + (√2)t] /[1 + (√2)t] = [- 1/(2√2)] ln |1 - (√2)t| + [1/(2√2)] ln |1 + (√2)t| + C = [1/(2√2)] [ln |1 + (√2)t| - ln |1 - (√2)t|] + C = recalling logarithms properties, [1/(2√2)] ln |[1 + (√2)t] /[1 - (√2)t]| + C thus, substituiting back sinx for t, you have: ∫ [cosx /(1 - 2sin²x)] dx = [1/(2√2)] ln |[1 + (√2)sinx] /[1 - (√2)sinx]| + C (##) the solution of the latter integral (see expression (#) above) is similar: ∫ [- sinx /(2cos²x - 1)] dx = let cosx = u → d(cosx) = du → - sinx dx = du ∫ [- sinx /(2cos²x - 1)] dx = ∫ du /(2u² - 1) = ∫ du /[(√2)u]² - 1] = ∫ du /{[(√2)u - 1][(√2)u + 1]} partial fraction decomposition 1 /{[(√2)u - 1][(√2)u + 1]} = A/[(√2)u - 1] + B/[(√2)u + 1] 1 /{[(√2)u - 1][(√2)u + 1]} = {A[(√2)u + 1] + B[(√2)u - 1]} /{[(√2)u - 1][(√2)u + 1]} 1 = A[(√2)u + 1] + B[(√2)u - 1] 1 = (√2)Au + A + (√2)Bu - B 1 = (√2)(A + B)u + (A - B) | (√2)(A + B) = 0 | A - B = 1 | A = - B | - B - B = 1 | A = 1/2 | B = - 1/2 yielding: 1 /{[(√2)u - 1][(√2)u + 1]} = A/[(√2)u - 1] + B/[(√2)u + 1] = (1/2)/[(√2)u - 1] - (1/2)/[(√2)u + 1] hence: ∫ du /(2u² - 1) = ∫ {{(1/2)/[(√2)u - 1]} - {(1/2)/[(√2)u + 1]}} du = (1/2) ∫ du /[(√2)u - 1] - (1/2) ∫ du /[(√2)u + 1] = dividing and multiplying by √2, (1/2)(1/√2) ∫ (√2) du /[(√2)u - 1] - (1/2)(1/√2) ∫ (√2) du /[(√2)u + 1] = [1/(2√2)] ∫ d[(√2)u - 1] /[(√2)u - 1] - [1/(2√2)] ∫ d[(√2)u + 1] /[(√2)u + 1] = [1/(2√2)] ln |(√2)u - 1| - [1/(2√2)] ln |(√2)u + 1| + C = [1/(2√2)] [ln |(√2)u - 1| - ln |(√2)u + 1|] + C = [1/(2√2)] ln |[(√2)u - 1] /[(√2)u + 1]| + C = substituiting back cosx for u, ∫ [- sinx /(2cos²x - 1)] dx = [1/(2√2)] ln |[(√2)cosx - 1] /[(√2)cosx + 1]| + C (###) thus, plugging this and the previous (###) result into the above (#) expression, you have: ∫ [cosx /(1 - 2sin²x)] dx + ∫ [- sinx /(2cos²x - 1)] dx = [1/(2√2)] ln |[1 + (√2)sinx] /[1 - (√2)sinx]| + [1/(2√2)] ln |[(√2)cosx - 1] /[(√2)cosx + 1]| + C = [1/(2√2)] {ln |[1 + (√2)sinx] /[1 - (√2)sinx]| + ln |[(√2)cosx - 1] /[(√2)cosx + 1]|} + C = owing to logarithm properties, [1/(2√2)] ln |{[1 + (√2)sinx] /[1 - (√2)sinx]}{[(√2)cosx - 1] /[(√2)cosx + 1]|} + C thus, in conclusion: ∫ [1 /(cosx + sinx)] dx = [1/(2√2)] ln |{[1 + (√2)sinx][(√2)cosx - 1]} /{[1 - (√2)sinx][(√2)cosx + 1]}| + C
Tags: integrate 1/(sinx + cosx) dx
Subscribe
  • Post a new comment

    Error

    default userpic

    Your reply will be screened

    Your IP address will be recorded 

    When you submit the form an invisible reCAPTCHA check will be performed.
    You must follow the Privacy Policy and Google Terms of use.
  • 0 comments